Mutagenic and genotoxic effects induced by PM0.5 of different Italian towns in human cells and bacteria: The MAPEC_LIFE study. (February 2019) - ; Gilli, G.; Romanazzi, V.; Gea, M.; Festa, A.; Viola, G.C.V.; Zani, C.; Zerbini, I.; Donato, F.; Monarca, S.; Fatigoni, C.; Levorato, S.; et al.
Abstract: Particulate matter (PM) is considered an atmospheric pollutant that mostly affects human health. The finest fractions of PM (PM2.5 or less) play a major role in causing chronic diseases. The aim of this study was to investigate the genotoxic effects of PM0.5 collected in five Italian towns using different bioassays. The role of chemical composition on the genotoxicity induced was also evaluated. The present study was included in the multicentre MAPEC_LIFE project, which aimed to evaluate the associations between air pollution exposure and early biological effects in Italian children. PM10 samples were collected in 2 seasons (winter and spring) using a high-volume multistage cascade impactor. The results showed that PM0.5 represents a very high proportion of PM10 (range 10–63%). PM0.5 organic extracts were chemically analysed (PAHs, nitro-PAHs ) and tested by the comet assay (A549 and BEAS-2B cells), MN test (A549 cells) and Ames test on Salmonella strains (TA100, TA98, TA98NR and YG1021). The highest concentrations of PAHs and nitro-PAHs in PM0.5 were observed in the Torino, Brescia and Pisa samples in winter. The Ames test showed low mutagenic activity. The highest net revertants/m 3 were observed in the Torino and Brescia samples (winter), and the mutagenic effect was associated with PM0.5 (p < 0.01), PAH and nitro-PAH (p < 0.05) concentrations. The YG1021 strain showed the highest sensitivity to PM0.5 samples. No genotoxic effect of PM0.5 extracts was observed using A549 cells except for some samples in winter (comet assay), while BEAS-2B cells showed light DNA damage in the Torino, Brescia and Pisa samples in winter, highlighting the higher sensitivity of BEAS-2B cells, which was consistent with the Ames test (p < 0.01). The results obtained showed that it is important to further investigate the finest fractions of PM, which represent a relevant percentage of PM10, taking into account the chemical composition and the biological effects induced. Graphical abstract: Highlights: The genotoxic effects of PM0.5 collected in 5 Italian towns were evaluated. PM0.5 represents a very high proportion of PM10 . PM0.5 organic extracts induced low mutagenic and genotoxic effects. The YG1021 strain and BEAS-2B cells showed a greater sensitivity to PM0.5 samples. The biological effects were associated with levels of PM0.5, PAHs and nitro-PAHs. Abstract : Results highlighted the importance to further investigate the finest fractions of PM, which represent a relevant percentage of PM10, taking into account its chemical composition and the biological effects induced.